THE CONCEPT OF DEVELOPING DESIGN COMPETENCIES IN FUTURE TEACHERS (Scientific journal of the Fergana State University, 2024)
This article pays special attention to ensuring the effectiveness of education through the effective use of pedagogical design methodology in the content of education, which is the driving force for the development of the state. Thoughts about interest in the formation of project activities of schoolchildren and students in the modern educational process are highlighted.